The Body as Resistance: The Naked Body Movement of Women in Nusa Tenggara Timur as A Political Action from Hannah Arendt’s Perspective - Tan, Petrus; Jegalus, Norbertus (International Journal of Indonesian Philosophy & Theology, 2025)
In recent years, the naked body movement as a form of women’s resistance against the expansion of the extractive industries in Nusa Tenggara Timur (NTT) has drawn less attention from academics. This movement significantly redefines women's public roles and drives social development. This research explores the meaning of women's naked body movement based on Hannah Arendt’s theory of action. This research uses a qualitative approach, including a literature review, a document study, and critical analysis. This study indicates that the women's naked body movement in NTT is a political action because it is challenging and subverting structural and political injustice, transforming the negative association of nudity into positive power. This movement transforms the woman's body from a laboring and working body to a political body. This politicization of sexuality has drawn public attention to the female body, making it a form of politics itself. The transformation redefines the female body as a powerful site of resistance against state authority, capitalist exploitation, and patriarchal control.